INTEGRASI METODE FUZZY FMEA DAN AHP DALAM ANALISIS DAN MITIGASI RISIKO RANTAI PASOK BAWANG MERAH [Integration Fuzzy FMEA and AHP Method in Risk Management of Shallot Supply Chain] - Erwin Arya Winanto; Imam Santoso (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2017)
This study aimed to identify, determine and formulate the mitigation strategies of shallot supply chain risk using Fuzzy FMEA and AHP. Risk identification was performed on shallot supply chain actors include farmers (suppliers), tengkulak (distributors) and pengecer (retailers). Fuzzy FMEA was used as a tool to measure the risks identified priorities. AHP was used as a tool for determining the weighting strategies in supply chain risk mitigation strategies. Research showed that there were some risks identified on the perpetrators of the supply chain in terms of supply and demand. Risk priorities for supply chain farmers (suppliers) were risks associated with government policies that were policies related to shallot imports, the risk priority of middlemen (distributors) supply chain was risks associated with shallot imports competition, and the risk priority of retailers supply chain was a risk for competitor with other retailers. There were six alternative mitigation strategies, and the highest priority was choosing the right varieties, followed by a partnership, improve the promotion, maintain quality, maintain price stability, and maintain supplies.Keywords: AHP, Fuzzy FMEA, Risk Management, Shallot.